Perencanaan Lampu Penerangan Jalan Menggunakan Turbin Angin Sumbu Vertikal Savonius - Mualifi Usman; Kadaryono Kadaryono; Maulana Dwi Hariska; Machrus Ali (Jurnal FORTECH, 2023)
Electricity is a basic need for almost all human beings, electricity is the main requirement in all economic activities and human activities. The diminishing availability of fossil fuels requires alternative energy sources that can meet energy needs. In this research, a micro-scale power plant for street lighting was developed, using a vertical wind turbine. To obtain mechanical energy from wind power, a vertical wind turbine of the Savonius type was developed. A single phase rectifier is used to convert the generator's mains voltage into direct current which is supplied to the battery for energy storage purposes. An LDR (Light Dependent Resistor) based automatic switch is used which functions to turn on the lights when it is dark. With the alternative of using a wind turbine for street lighting, it has the advantage of being able to keep generating electricity 24 hours a day, as long as there is wind from the vehicles passing through it. After doing research, this wind turbine can produce a voltage of 12.2 volts at a wind speed of 3.85 m/s, suitable for use in small-scale power plants. This type of power plant can be further developed on a larger scale so that it can be utilized to supply electrical energy needs in areas that are still not covered by electricity